Effect of Cobalt Ferrite Nanoparticles Synthesized with Sumac Extract on Changes in Biochemical and Histological Factors in Rats - Morteza Ghasemi; Fariba Mahmoudi; Arash Abdolmaleki; Milad Soluki (مجله دانشگاه علوم پزشکی گرگان, 2023)
Background and Objective: The application of different nanoparticles using green synthesis is increasing due to fewer complications. This study was conducted to identify the effect of cobalt ferrite nanoparticles synthesized with sumac extract on changes in biochemical and histological factors in rats. Methods: In this experimental study, 30 five-month-old male Wistar rats with an approximate weight of 250-300 mg/kg of body weight were divided into three groups: The control group (saline receiving), the experimental groups receiving intraperitoneal cobalt ferrite nanoparticles synthesized with sumac extract at a dose of 10 and 20 mg/kg of body weight. Serum and tissue samples (liver, kidney, and spleen) were isolated. Serum concentrations of urea, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatinine were determined. The photometric method was used to measure liver enzymes, the calorimetric method without omitting proteins based on the Jaffe method was used to measure creatinine, and the urease-glutamate dehydrogenase (GLDH) method was used to measure urea. Tissue samples were assessed by hematoxylin-eosin staining. Transmission electron microscopy (TEM) and scanning electron microscope (SEM) microscopic studies were used for microscopic investigations. Results: No statistical significance was observed in blood samples and factors (urea, creatinine, ALT, and AST) in the experimental groups compared to the control group. Similarly, in the morphological investigation, the size of the liver, kidney, and spleen of the groups receiving cobalt ferrite nanoparticles synthesized with sumac extract was normal compared to the control group. Conclusion: Cobalt ferrite nanoparticles synthesized with sumac had no toxic effect on the rats’ liver, spleen, and kidney tissues.